Regenerative potentials of bone marrow mesenchymal stem cells derived exosomes or its combination with zinc in recovery of degenerated circumvallate papilla following surgical bilateral transection of glossopharyngeal nerve in rats - Eman Mohamed Salem; Hamdy Rizk; Yara S. Abouelela; Abdelbary Prince; Adel Fathy Tohamy; Nawal A. Lasheen; Bassant A. Ezzat; Sana Mostafa (BMC, 2024)
Abstract Background Taste buds' innervation is necessary to sustain their cell turnover, differentiated taste buds and nerve fibers in circumvallate papilla (CVP) disappear following glossopharyngeal nerve transection. Normally, taste buds recover to baseline number in about 70 days. Bone marrow stem cell (BM-MSC) derived exosomes or their combination with Zinc chloride are used to assess their potential to speed up the regeneration process of CVP following bilateral deafferentation. Methods Twenty-eight male Sprague-Dawley rats were randomly divided into four groups; Group I: subjected to sham operation followed by IP injection of saline. The other experimental groups (II, III and IV) were subjected to surgical bilateral transection of glossopharyngeal nerve. Group II received single IP injection of saline. Group III received single IV injection of BM-MSC-derived exosomes (100 µg). Group IV received single IV injection of BM-MSC-derived exosomes and single IP injection of zinc chloride (5 mg/kg). After 28 days, CVP was dissected and prepared for histological and histomorphometric analysis, RT-PCR for cytokeratin 8 gene expression, ELISA to assess protein level of brain-derived neurotrophic factor, redox state analysis of malondialdehyde and glutathione content, followed by statistical analysis. Results Histopathologically, group II exhibited great tissue damage with marked reduction in taste buds and signs of degeneration in the remaining ones. Group III was close to control group with marked improvement in taste buds' number and structure. Group IV showed inferior results when compared to group III, with many immature taste buds and signs of degeneration. Statistical results showed that groups I and III have significantly higher values than groups II and IV regarding taste buds' number, cytokeratin 8, and reduced glutathione. However, malondialdehyde demonstrated high significant values in group IV compared to groups I and III. Regarding brain-derived neurotrophic factor, group III had significantly higher values than group II. Conclusion BM-MSC-derived exosomes have superior regenerative potentials in acceleration of CVP and nerve healing following bilateral transection of glossopharyngeal nerve in contrary to its combination with zinc chloride. Graphical Abstract